2022
DOI: 10.3389/fpsyg.2022.972006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parenting styles on undergraduate students’ emotion regulation: The mediating role of academic-social student-faculty interaction

Abstract: Based on the survey data of 4,462 undergraduate students in Zhejiang Province, mainland China, this study investigated the influence of parenting styles on emotion regulation and the mediating role of student-faculty interaction. The study found that: (1) Male students scored significantly higher than female students on emotion regulation, overprotective parenting style and student-faculty interaction. (2) Parenting style has a direct positive effect on emotion regulation, and warm parenting style has a much g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Social and emotional competence is cultivated and developed in the interaction of individuals, families, schools, and other systems. Existing studies have paid more attention to the cultivation of students' social and emotional abilities in the basic education stage, and found that school belonging (Tang and Huang, 2023) [5], growth, thinking and learning (Huang et al, 2023) [6], and family rearing style (Yao and Chen, 2022) [7] can affect students' social and emotional abilities to varying degrees. In addition, the classroom environment is one of the main driving factors for the effective implementation of social and emotional education, complementing and strengthening the social and emotional abilities taught in the curriculum (Cefai et al, 2018) [8].…”
Section: Factors Affecting Social and Emotional Competencementioning
confidence: 99%
“…Social and emotional competence is cultivated and developed in the interaction of individuals, families, schools, and other systems. Existing studies have paid more attention to the cultivation of students' social and emotional abilities in the basic education stage, and found that school belonging (Tang and Huang, 2023) [5], growth, thinking and learning (Huang et al, 2023) [6], and family rearing style (Yao and Chen, 2022) [7] can affect students' social and emotional abilities to varying degrees. In addition, the classroom environment is one of the main driving factors for the effective implementation of social and emotional education, complementing and strengthening the social and emotional abilities taught in the curriculum (Cefai et al, 2018) [8].…”
Section: Factors Affecting Social and Emotional Competencementioning
confidence: 99%
“…Guo and Wang (2022) believed that classroom teaching plays an important role in guiding students to carry out social and emotional learning, forming correct social concepts, establishing social responsibility, and developing social literacy, and pointed out that the contents of social and emotional learning in classroom teaching include four aspects: the social sense of reason, social morality, social aesthetic feeling, and social responsibility [15]. Yao and Chen (2022) discussed the influence of different family-rearing patterns on college students' social and emotional competence and pointed out that schools can produce substitution effects to make up for the deficiency of family rearing in cultivating college students' social and emotional competence [16]. Tang and Huang (2023) based on SSES data, through empirical research, found that school belonging plays an important role in promoting the effectiveness of social and emotional competence training in primary and secondary schools [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, Li, Dewaele, and Jiang [ 16 ] noted that students who have control over their positive and negative emotions are more likely to succeed in educational settings. Notwithstanding the significant role of emotion regulation in language learners’ academic performance [ 13 , 15 ], little attention has been directed toward the predictors of this construct in language classes [ 17 , 18 , 19 , 20 ]. Moreover, PP variables influencing language learners’ emotion regulation have somehow been disregarded by previous scholars.…”
Section: Introductionmentioning
confidence: 99%